(untitled) (Fiep Bulletin - online, 2013)
Down Syndrome (SD) the is regarded as the more common of the genetic anomalies and mental deficiencies, which can be identified either at prenatal diagnosis or clinically by the phenotype of the newly born. The precocious diagnosis in DS is crucial, due to several congenital malformations and late complications associated to the Syndrome. Based on this presupposition, the objective of this research was to study the dermatoglyphic and anthropometric features of individuals with Down Syndrome (DS) assisted by the Integrated Center for supporting people with Deficiency - FUNAD in the city of João Pessoa - PB. A sample, consisting of 21 subjects males and female with age group from 6 to 30 years, was evaluated. The fingerprints were collected through the protocol of Cummins and Midlo (1961) and the anthropometric characteristics of the body mass and stature were evaluated. A descriptive methodology of traversal feature was used to analyze the results expressed through the measures of central tendency and standard deviation, respectively, that identified the following values: age (16,33 ± 7,84) years; body mass (48,55 ± 19,90) kg; stature (139,55 ± 17,19) cm; BMI (23,52 ± 6,28) kg/m2; D10 (11,33 ± 2,50); SQTL (130,14 ± 35,87); SQTLE (64,95 ± 17,21); SQTLD (65,19 ± 19,47). In the qualitative dermatoglyphic features, the following percentages were verified: Arch " A " (4,3%); Loop " L " (78,1%); Whorl " W " (17,6%). Based on the interpretation of those results it was concluded that 77,7% of the male group were above the weight. Only 33,3% of the women were classified in this pattern and that the men maintained a stature pattern superior to the women´s . A prevalence of the drawing of the loop (L) was observed in the dermatoglyphic features in the fingers of the hands. Hence, it could be concluded that this simple technique can be a valuable tool to characterize the individuals with DS.